Inhibition of PDIA3 in club cells attenuates osteopontin production and lung fibrosis. Issue 7 (16th August 2021) - Kumar, Amit; Elko, Evan; Bruno, Sierra R; Mark, Zoe F; Chamberlain, Nicolas; Mihavics, Bethany Korwin; Chandrasekaran, Ravishankar; Walzer, Joseph; Ruban, Mona; Gold, Clarissa; Lam, Ying Wai; Ghandikota, Sudhir; et al.
Abstract : Background: The role of club cells in the pathology of idiopathic pulmonary fibrosis (IPF) is not well understood. Protein disulfide isomerase A3 (PDIA3), an endoplasmic reticulum-based redox chaperone required for the functions of various fibrosis-related proteins; however, the mechanisms of action of PDIA3 in pulmonary fibrosis are not fully elucidated. Objectives: To examine the role of club cells and PDIA3 in the pathology of pulmonary fibrosis and the therapeutic potential of inhibition of PDIA3 in lung fibrosis. Methods: Role of PDIA3 and aberrant club cells in lung fibrosis was studied by analyses of human transcriptome dataset from Lung Genomics Research Consortium, other public resources, the specific deletion or inhibition of PDIA3 in club cells and blocking SPP1 downstream of PDIA3 in mice. Results: PDIA3 and club cell secretory protein ( SCGB1A1 ) signatures are upregulated in IPF compared with control patients. PDIA3 or SCGB1A1 increases also correlate with a decrease in lung function in patients with IPF. The bleomycin (BLM) model of lung fibrosis showed increases in PDIA3 in SCGB1A1 cells in the lung parenchyma. Ablation of Pdia3, specifically in SCGB1A1 cells, decreases parenchymal SCGB1A1 cells along with fibrosis in mice. The administration of a PDI inhibitor LOC14 reversed the BLM-induced parenchymal SCGB1A1 cells and fibrosis in mice. Evaluation of PDIA3 partners revealed that SPP1 is a major interactor in fibrosis. Blocking SPP1 attenuated the development of lung fibrosis in mice. Conclusions: Our study reveals a new relationship with distally localised club cells, PDIA3 and SPP1 in lung fibrosis and inhibition of PDIA3 or SPP1 attenuates lung fibrosis.